Skeletal Muscle-Selective Knockout of LKB1 Increases Insulin Sensitivity, Improves Glucose Homeostasis, and Decreases TRB3 - Koh, Ho-Jin (American Society for Microbiology, 2006)
LKB1 is a tumor suppressor that may also be fundamental to cell metabolism, since LKB1 phosphorylates and activates the energy sensing enzyme AMPK. We generated muscle-specific LKB1 knockout (MLKB1KO) mice, and surprisingly, found that a lack of LKB1 in skeletal muscle enhanced insulin sensitivity, as evidenced by decreased fasting glucose and insulin concentrations, improved glucose tolerance, increased muscle glucose uptake in vivo, and increased glucose utilization during a hyperinsulinemic-euglycemic clamp. MLKB1KO mice had increased insulin-stimulated Akt phosphorylation and a >80% decrease in muscle expression of TRB3, a recently identified Akt inhibitor. Akt/TRB3 binding was present in skeletal muscle, and overexpression of TRB3 in C2C12 myoblasts significantly reduced Akt phosphorylation. These results demonstrate that skeletal muscle LKB1 is a negative regulator of insulin sensitivity and glucose homeostasis. LKB1-mediated TRB3 expression provides a novel link between LKB1 and Akt, critical kinases involved in both tumor genesis and cell metabolism.